Viscosity of NaAlSi3O8−H2O fluids and implications for arc magmatism - Yang Li; Lars Stixrude; Craig E. Manning; Jie Deng (Earth and Planetary Science Letters, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

Seawater mixing as a mechanism to enrich gold ore: Insights from the Ludousou gold deposit (China) - Hao-Cheng Yu; Jun Deng; Kun-Feng Qiu; A. E. Williams-Jones; Ya-Qi Huang; Lian Zhang; Lei Wang; Ke Geng; Xiao-Fei Yu; Deng-Yang He; Jia-Dong Ma; Yong-Sheng Li (Mineralium Deposita, 2026)

Co-evolution of marine ecosystems and nutrient cycles during the Great Ordovician Biodiversification Event - Shengchao Yang; Thomas J. Algeo; Thomas Servais; Ronald E. Martin; David A.T. Harper; Charles R. Marshall; Yiying Deng; Zongyuan Sun; Zhengbo Lu; Jian Cao; Chao Li; Shu-zhong Shen; et al. (Earth and Planetary Science Letters, 2026)

Coupling effect of urban building clusters and crosswinds on the aerodynamic performance of high-speed maglev trains - Jianfeng Mao; Xi Wang; Yikang Liu; Zhiwu Yu; Zheng Li; E Deng (Sustainable Cities and Society, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Fe-based monometallic and bimetallic carbon nanocatalyst for efficient adsorption and degradation of doxycycline via peroxymonosulfate activation - Qiaoping Kong; Jing Yu; Mengyuan Deng; Bingbing Song; Shixiong Li; Weiwei Ma; Tong Yu; Xueqing Shi; Tuo Wei; Jianjun Lian; Basem E. Keshta (Journal of Environmental Chemical Engineering, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Intensified rainfall overrides vegetation greening in driving erosion and carbon loss on the Tibetan Plateau - Rui Deng; Dongfeng Li; Yi Zhao; Desmond E. Walling; Panos Panagos; Pasquale Borrelli; Philippe Ciais; Yuefei Huang; Yuanyuan Bai; Sergey Chalov; Valentin N. Golosov; Xudong Fu; et al. (Science Bulletin, 2025)

Quality changes in the physiology, behaviour, nutrition, and taste of Urechis unicinctus during waterless live transportation - Teng Teng; Yuchun Lu; Zichen Deng; Shuqi Wang; Yuting Yang; Huihong Li; Chun-E Liu (Food Chemistry, 2025)

Methane adsorption capacity of shale in the upper Permian Longtan Formation in the eastern Sichuan–northern Guizhou region, South China - X-M. Li; X. Tang; S-B. Guo; Y-S. Shan; E-D. Deng; C-L. Lan; B-D. Tan (Australian Journal of Earth Sciences, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Polymetallic Te-rich melts contribute to efficient enrichment and precipitation of Au in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ri-Chen Zhong; Sarah A. Gleeson; Zhuo-Sen Yao; Daniel E. Harlov; Xiao-Dong Deng; Hao Cui; Chang Yu; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Healthy lifestyles ameliorate an increased risk of periodontitis associated with polycyclic aromatic hydrocarbons - An Li; Yuntao Chen; Mi Du; Ke Deng; Xin Cui; Chunhua Lin; Geerten-Has E. Tjakkes; Xiaodong Zhuang; Shixian Hu (Chemosphere, 2024)

Air pollution mixture associated with oxidative stress exacerbation and symptoms deterioration in allergic rhinitis patients: Evidence from a panel study - Jinhui Li; Haisheng Wu; Weiwei Xing; Xin Li; Zheshen Han; Renyue Ji; Zhengyi Deng; Minji Jung; Shengzhi Sun; Benjamin I. Chung; Andres Cardenas; Marvin E. Langston (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Gut microbiota influence frailty syndrome in older adults: mechanisms and therapeutic strategies - Xiao-Ming Wang; Lu Fan; Chen-Chen Meng; Yun-Jiao Wang; Li-E Deng; Zhuo Yuan; Jun-Ping Zhang; Yan-Yang Li; Shi-Chao Lv (Biogerontology, 2024)

Annual greenhouse gas emissions from a rice paddy with different water-nitrogen management strategies in Central China - Jianling Li; Yu’e Li; Yunfan Wan; Bin Wang; Weiwei Cai; Xiaobo Qin; Zhihua Zhou; Xingyu Wang; Jianing Yuan; Qi Deng (Soil and Tillage Research, 2024)

Dust diffusion laws during partition excavation by boom-type roadheader in a metro tunnel - Ning Liu; Xiong Wu; E Deng; Yi-Qing Ni; Wei-Chao Yang; Guo-Zhi Li (Tunnelling and Underground Space Technology, 2023)

Co-generation of hydroxyl and sulfate radicals via homogeneous and heterogeneous bi-catalysis with the EO-PS-EF tri-coupling system for efficient removal of refractory organic pollutants - Wanlin Yang; Zejun Deng; Libin Liu; Kechao Zhou; Sharel P. E; Lingcong Meng; Li Ma; Qiuping Wei (Water Research, 2023)

Tumor-derived microparticles-based nanomaterial as platform for delivery of tumor antigens to enhance immunogenicity - Qi Tan; Zimo Yang; Shichen Bu; Jiangbin Chen; Wenjuan Chen; Wei Geng; Qi Huang; Limin Duan; Mengfei Guo; Yali Wu; Jingjing Deng; E Zhou; et al. (Chemical Engineering Journal, 2023)

Re-evaluation of equilibrium relationships involving U6+/U4+ and Fe3+/Fe2+ in hydrothermal fluids and their implications for U mineralization - Teng Deng; Guoxiang Chi; Anthony E. Williams-Jones; Zenghua Li; Yumeng Wang; Deru Xu; Zhilin Wang (Chemical Geology, 2023)

Tumor cell-derived microparticles packaging monocarboxylate transporter4 inhibitor fluvastatin suppress lung adenocarcinoma via tumor microenvironment remodeling and improve chemotherapy - Wenjuan Chen; Qi Tan; Mengfei Guo; Tingting Liao; Yumei Li; Zhengrong Yin; E. Zhou; Jingjing Deng; Minglei Li; Zimo Yang; Jiangbin Chen; Jiaping Chen; et al. (Chemical Engineering Journal, 2023)

Spartina alterniflora saltmarsh soil organic carbon properties and sources in coastal wetlands - Jin-e Liu; Dailan Deng; Caiyu Zou; Ruiming Han; Yue Xin; Zihao Shu; Li-min Zhang (Journal of Soils and Sediments, 2021)

Initial ingestion of CMV-infected plants reduces subsequent aphid performance - Xiao-bin Shi; Jun Deng; Zhuo Zhang; Shuo Yan; Li-min Zheng; Shu-e Sun; Yang Gao; Xu-guo Zhou; De-yong Zhang; Yong Liu (Arthropod-Plant Interactions, 2021)

Whole-cell bioreporters for evaluating petroleum hydrocarbon contamination - Bo Jiang; Yizhi Song; Zengjun Liu; Wei E. Huang; Guanghe Li; Songqiang Deng; Yi Xing; Dayi Zhang (Critical Reviews in Environmental Science and Technology, 2021)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

A novel variant of Gh_D02G0276 is required for root-knot nematode resistance on chromosome 14 (D02) in Upland cotton - Martin J. Wubben; Gregory N. Thyssen; Franklin E. Callahan; David D. Fang; Dewayne D. Deng; Jack C. McCarty; Ping Li; Md Sariful Islam; Johnie N. Jenkins (Theoretical and Applied Genetics, 2019)

Evolution of interspecies unilateral incompatibility in the relatives of Arabidopsis thaliana - Ling Li; Bo Liu; Xiaomei Deng; Hainan Zhao; Hongyan Li; Shilai Xing; Della D. Fetzer; Mengya Li; Mikhail E. Nasrallah; June B. Nasrallah; Pei Liu (Molecular Ecology, 2018)
The evolutionary concurrence of intraspecies self‐incompatibility ( SI ) and explosive angiosperm radiation in the Cretaceous have led to the hypothesis that SI was one of the predominant drivers of rapid speciation in angiosperms. Interspecies unilateral incompatibility ( UI ) usually occurs when pollen from a self‐compatible ( SC ) species is rejected by the pistils of a SI species, while the reciprocal pollination is compatible ( UC ). Although this SI × SC type UI is most prevalent and viewed as a prezygotic isolation barrier to promote incipient speciation of angiosperms, comparative evidence to support such a role is lacking. We show that SI × SI type UI in SI species pairs is also common in the well‐characterized accessions representing the four major lineages of the Arabidopsis genus and is developmentally regulated. This allowed us to reveal a strong correlation between UI strength and species divergence in these representative accessions. In addition, analyses of a SC accession and the pseudo‐self‐compatible ( psc ) spontaneous mutant of Arabidopsis lyrata indicate that UI shares, at least, common pollen rejection pathway with SI . Furthermore, genetic and genomic analyses of SI × SI type UI in A. lyrata × A. arenosa species pair showed that two major‐effect quantitative trait loci are the stigma and pollen‐side determinant of UI , respectively, which could be involved in heterospecies pollen discrimination. By revealing a close link between UI and SI pathway, particularly between UI and species divergence in these representative accessions, our findings establish a connection between SI and speciation. Thus, the pre‐existence of SI system would have facilitated the evolution of UI and accordingly promote speciation.

Responses of switchgrass soil respiration and its components to precipitation gradient in a mesocosm study - Chih-Li Yu; Dafeng Hui; Qi Deng; E. Kudjo Dzantor; Philip A. Fay; Weijun Shen; Yiqi Luo (Plant and Soil, 2017)

Antibacterial mechanism of high-mobility group nucleosomal-binding domain 2 on the Gram-negative bacteria Escherichia coli - Heng Li; Xiao-fei Shen; Xin-e Zhou; Yan-e Shi; Lu-xia Deng; Yi Ma; Xiao-ying Wang; Jing-yu Li; Ning Huang (Journal of Zhejiang University-SCIENCE B, 2017)

The population genomic landscape of human genetic structure, admixture history and local adaptation in Peninsular Malaysia - Lian Deng; Boon Peng Hoh; Dongsheng Lu; Ruiqing Fu; Maude E. Phipps; Shilin Li; Ab Rajab Nur-Shafawati; Wan Isa Hatin; Endom Ismail; Siti Shuhada Mokhtar; Li Jin; Bin Alwi Zilfalil; et al. (Human Genetics, 2014)

Identifying Explicit Formulation of Operating Rules for Multi-Reservoir Systems Using Genetic Programming - Liping Li; Pan Liu; David E. Rheinheimer; Chao Deng; Yanlai Zhou (Water Resources Management, 2014)

Towards a resistance management strategy for Helicoverpa armigera in Bt-cotton in northwestern China: an assessment of potential refuge crops - Zhao-Zhi Lu; Myron P. Zalucki; Lynda E. Perkins; Deng-Yuan Wang; Li-Li Wu (Journal of Pest Science, 2013)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Molecular characterization and expression patterns of Lbx1 in porcine skeletal muscle - Zhe Chao; Jian Wu; Rong Zheng; Feng-E. Li; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2011)

A SNP in the miR-27a gene is associated with litter size in pigs - B. Lei; S. Gao; L. F. Luo; X. Y. Xia; S. W. Jiang; C. Y. Deng; Y. Z. Xiong; F. E. Li (Molecular Biology Reports, 2011)

Real-time reverse transcription–PCR expression profiling of porcine troponin I family in three different types of muscles during development - H. Yang; Z. Y. Xu; M. G. Lei; F. E. Li; C. Y. Deng; Y. Z. Xiong; B. Zuo (Molecular Biology Reports, 2011)

Molecular cloning, tissue expression and association of porcine NR4A1 gene with reproductive traits - L. Q. Liu; F. E. Li; C. Y. Deng; Y. Z. Xiong (Molecular Biology Reports, 2011)

Identification of three novel SNPs and association with carcass traits in porcine TNNI1 and TNNI2 - Z. Y. Xu; H. Yang; Y. Z. Xiong; C. Y. Deng; F. E. Li; M. G. Lei; B. Zuo (Molecular Biology Reports, 2010)

Molecular characterization, expression profile and association analysis with carcass traits of porcine LCAT gene - Mu Qiao; Hua-Yu Wu; Feng-E Li; Si-Wen Jiang; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2010)

Association of 3 polymorphisms in porcine troponin I genes (TNNI1 andTNNI2) with meat quality traits - H. Yang; Z. Y. Xu; M. G. Lei; F. E. Li; C. Y. Deng; Y. Z. Xiong; B. Zuo (Journal of Applied Genetics, 2010)

Optimizing the shoot proliferation protocol of Penthorum chinense by axillary buds - Li-Qiang Wang; Jun Yang; E. Deng; Guang-Bi Wang; Zheng-Song Peng (Biotechnology Letters, 2008)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

A new aporphine alkaloid from Sabia yunnanensis - Yun Deng; Tian Jun Tang; Xiang Li; Feng. E Wu (Natural Product Research, 2007)

An Auxin-Inducible F-Box Protein CEGENDUO Negatively Regulates Auxin-Mediated Lateral Root Formation in Arabidopsis - Li Dong; Lei Wang; Yu’e Zhang; Yansheng Zhang; Xingwang Deng; Yongbiao Xue (Plant Molecular Biology, 2006)

Genome-wide analysis of S-Locus F-box-like genes in Arabidopsis thaliana - Lei Wang; Li Dong; Yu’e Zhang; Yansheng Zhang; Weihua Wu; Xingwang Deng; Yongbiao Xue (Plant Molecular Biology, 2004)